The Effect of Using Some Google Educational Applications in Teaching Computer Curriculum on the Achievement of Students for the First Year in College of Education, University of Samarra. - Abdul Munem. Hasan . Ahmed. Ali, Inst.; ., . (International Journal of Engineering and Technology, 2018)
The objective of this research is to find out the effect of the use of some Google educational applications in the process of teaching the computer curriculum on the achievement of students of the first year in college of Education / University of Samarra. The researcher used the semi-experimental method. The sample consisted of (38) male and female students The first year in the Department of biology at the college of Education, Samarra University, was divided into two groups, one experimental, consisting of (19) students and was studied using some Google educational applications through integrated education. The control group consisted of (19). I studied using the traditional method of curing Which is (the lecture method), note that the two groups (experimental and control) equal in number and unequal in the number of variables that could affect the safety of the design follicular Search, the researcher chose a number of topics related to the curriculum of the computer curriculum, which is taught to students of the first year in the college of Education, University of Samarra. These topics are (computer components, electronic penetration, computer virus, operating system). The teaching of objectives for each of these subjects was determined in light of the objectives of the researcher that used a set of research tools. it included (50) questionnaires, including (25 questions of the type of correctness and errors), (25 questions of multiple choice type), and the researcher used some Google educational applications in teaching group students (Google Gmail, Google Docs, Google sites, Google+, Google calendar), as well as a web site that includes curriculum materials for the computer curriculum. The researcher used a set of statistical methods including: arithmetic mean, standard deviation coefficient, T-Test) for independent samples, and the research reached the following results:There are statistically significant differences at the level of significance (0.05) between the mean scores of the experimental group and the scores of the control group students in the post-achievement test for the experimental group studied using some Google educational applications.In light of the findings of the current research, the researcher recommended a number of recommendations, including the need to use Google's educational applications in teaching computer curriculum in the colleges of education and need to provide Internet service in computer laboratories in universities.Â Â